PEMIKIRAN MUSDAH MULIA TENTANG KEPEMIMPINAN POLITIK PEREMPUAN - Hendri Saputra (Manthiq, 2016)
Abstract: Speaking role of women in the public sphere, as if it never finishes. This is because the role of women in the public sphere, especially  political role believed to be less significant. Until well into the third millennium, there  are some scholars and intellectuals who view the role of negative  and positive contribution of women in the political sphere. They do a textual interpretation of the Koran and the hadith which prohibits women involved in politics. Through constructive criticism and holistic reconstruction, this study attempts to explore  the political role of women in public space idea Musdah Mulia. For Musdah, the thing to do is not only the reconstruction of the interpretation of the fundamental doctrines of Islam (al-Quran  and Hadith), but also a practical movement in the  field of education, culture,  and  public  policy. All the  reconstruction of the  political  leadership role  of women should  be  carried out  simultaneously in order  to produce concrete changes. This is because there are a number of internal  factors  that cause women can  not have a significant role in the political sphere that includes the figure of a woman’s own diffident and passive to the opportunities that exist. They also lack support, chained stereotypes as the guardian of the domestic sphere, remained shut  misogynistic  tradition,  as well as the  interpretation of religious  bias  patriarchal values  and  gender bias. In this study the  authors use  historical methods-qualitative and  descriptive-analytic ie library research (library research) by studying,  describing and analyzing the writings Musdah Mulia either in the form of books like any research, and writings that discuss ideas Musdah Mulia on women’s leadership, as well as other  books  that are relevant  to the topic penulisbahas. The results  showed that in view Musdah Mulia women can play a role in any sphere, including  the public domain. In the political domain, women can  play an active role in politics, ranging from the general  election, active in a political party or participate in the realm  of legislative, executive and judicial. The basis of such  thinking is a) There is no difference in men  and women. b) The essence of Islam is to humanize human beings and respect for sovereignty. c) The essence of religious teachings is to humanize humans, respect of human and glorify it. No matter what race, ethnicity, color, gender and social status.  In fact, no matter what their religion; d) There is no prohibition in Islam related to women’s leadership in politics, even history records many women who play an active role both in the prophet and his companions at the time.